Evaluation of a new anaesthetist-led propofol sedation service for endoscopy within a UK day-case setting. Issue 1 (5th December 2012) - Murugesan, Senthil V; Davies, Mark W; Nicholson, Jill; Hughes, Mark; Haslam, Neil; Smart, Howard L; Sarkar, Sanchoy
Abstract : Introduction: The use of propofol in endoscopy is becoming more prevalent both in Europe and North America. Potential advantages over conscious sedation include controlled deep sedation for therapeutic endoscopy and improved patient satisfaction. A new anaesthetist-led propofol-based day-case sedation service was introduced within the endoscopy unit at the Royal Liverpool University Hospital in April 2011. Aims: To evaluate this new service of anaesthetist-led propofol-based sedation for safety, compliance with current guidelines and satisfaction (patient, anaesthetist and endoscopist). Design: A prospective, service evaluation audit of a new, weekly, anaesthetist-led propofol-based sedation service. Administrative records, anaesthetic notes and satisfaction scores (1=very dissatisfied; 5=very satisfied; patients, anaesthetists, endoscopists) and the 'patient journey' were evaluated for 40 consecutive patients treated over 18 weeks. Outcomes were measured against current British Society of Gastroenterology/Royal College of Anaesthetists guidelines. Results: All procedures were completed (100% intention-to-treat rate), all patients were discharged on the day of the procedure and none were readmitted within 7 days. Adverse events were minor (10%) and there were no deaths within 30 days. The median satisfaction score was 5 for patients, anaesthetists and endoscopists. The additional cost for provision of such a service included the services of the anaesthetist (one programmed activity) and operating department personnel and for drugs (propofol). The demand for the service rapidly increased. Conclusions: Anaesthetist-led propofol-assisted endoscopy is safe in a day-case endoscopy unit and is associated with high satisfaction scores for patients, anaesthetists and endoscopists. There is a high demand for this service in this UK endoscopy day-case unit.